The Death and Resurrection of Deviance
XI, 327 p.
Keywords: Are reports of the 'death of deviance' premature? This collection brings together leading international scholars to analyse uses of the 'deviance' concept to argue its vitality and show its possible utility in a variety of fields including religion, education and media narratives.